Drift and confusion reign in Indian politics. . [article]. - Sridharan, Eswaran
"The prospect of India without a stable governing coalition-whether established by the Congress Party, by the BJP, or by regional parties supported by either the Congress or the BJP-is not beyond the realm of possibility." -(from the author)